Lithium ion battery, preparation method thereof and electric equipment

By forming a solid electrolyte interface mask with high content of Li2O and Li2CO3 on the negative electrode surface of the lithium-ion battery, the problem of reduced battery life in a low temperature environment is solved, and a higher low-temperature discharge efficiency and battery life are achieved.

CN119495797APending Publication Date: 2025-02-21CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311054882.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The discharge capacity of lithium-ion batteries in low temperature environments decreases, resulting in a significant reduction in battery life and affecting the user experience.

Method used

By forming a solid electrolyte interface mask (SEI) on the negative electrode surface of the lithium-ion battery, the content of Li2O and Li2CO3 is relatively high, which significantly improves the low-temperature performance of the battery.

Benefits of technology

Significantly reduce the impedance of lithium-ion batteries, especially in low-temperature environments, improve the discharge efficiency of the positive electrode active material, and improve the low-temperature discharge capacity and battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004414489890000151
    Figure BDA0004414489890000151
Patent Text Reader

Abstract

The invention provides a lithium ion battery, a preparation method thereof and electric equipment. The lithium ion battery comprises a negative electrode, wherein the surface of the negative electrode is provided with a solid electrolyte interface film; wherein the solid electrolyte interface film comprises lithium oxide and lithium carbonate; the mass percentage content of the sum of the mass of the lithium oxide and the mass of the lithium carbonate in the solid electrolyte interfacial film is greater than or equal to 20%. The lithium ion battery has relatively good low-temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the field of battery technology, and specifically to lithium-ion batteries and methods for preparing the same, and electrical equipment. Background Art

[0002] The discharge capacity of lithium-ion batteries is affected by temperature. The discharge capacity at low temperatures will be reduced to a certain extent, resulting in a significant reduction in the battery life in low temperature environments, which seriously affects the user experience. Therefore, it is urgent to reduce the impedance of lithium-ion batteries, especially the impedance at low temperatures, in order to improve the battery life of lithium-ion batteries at low temperatures. Summary of the invention

[0003] In view of this, the present invention provides a lithium-ion battery, wherein the solid electrolyte interface (SEI) film on the negative electrode surface of the lithium-ion battery has a Li 2 O and Li 2 CO 3 The high content can improve the low-temperature performance of lithium-ion batteries.

[0004] In a first aspect, the present application provides a lithium ion battery, comprising a negative electrode, the surface of the negative electrode having a solid electrolyte interface film;

[0005] Wherein, the solid electrolyte interface film includes lithium oxide and lithium carbonate;

[0006] The mass percentage of the sum of the mass of the lithium oxide and the lithium carbonate in the solid electrolyte interface film is greater than or equal to 20%.

[0007] In this battery, the sum of the masses of lithium oxide and lithium carbonate accounts for a significantly higher proportion in the SEI film than the SEI film in the prior art, which can significantly reduce the impedance of lithium-ion batteries, especially inhibit the impedance growth of lithium-ion batteries in low temperature environments, thereby improving the discharge efficiency of positive electrode active materials at low temperatures, improving the low-temperature discharge capability of the battery, and further improving the battery's endurance at low temperatures, significantly improving the battery's market competitiveness.

[0008] Optionally, the sum of the mass percentages of the lithium oxide and the lithium carbonate in the solid electrolyte interface film is 20%-60%.

[0009] Optionally, the mass percentage of the lithium oxide in the solid electrolyte interface film is 10%-25%.

[0010] Optionally, the mass percentage of the lithium carbonate in the solid electrolyte interface membrane is 10%-35%.

[0011] Optionally, the lithium-ion battery also includes a positive electrode, the surface of the positive electrode has a positive electrode electrolyte interface film; wherein the positive electrode electrolyte interface film includes lithium oxide and lithium carbonate; the sum of the mass percentages of the lithium oxide and lithium carbonate in the positive electrode electrolyte interface film is greater than or equal to 20%.

[0012] Optionally, the lithium-ion battery also includes a positive electrode, which includes a positive electrode collector and a positive electrode material layer stacked on the surface of the positive electrode collector, and the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes at least one of a phosphate-based positive electrode active material and a transition metal oxide positive electrode active material.

[0013] A second aspect of the present application is a method for preparing a lithium ion battery, comprising:

[0014] Providing a battery cell; and, persulfate is added to the battery cell;

[0015] The battery core is subjected to chemical formation to obtain the lithium-ion battery.

[0016] The preparation method has simple steps and strong process reliability, and can realize large-scale industrial production.

[0017] Optionally, the lithium-ion battery is the lithium-ion battery provided in the first aspect of the present application.

[0018] Optionally, the formation temperature is in the range of 20°C-70°C.

[0019] Optionally, the charging method used in the formation includes:

[0020] The battery cell is charged at a constant current of 0.03C-0.1C to 10% SOC-20% SOC, then charged at a constant current of 0.2C-0.5C to 3.5V-3.8V, and then charged at a constant current of 0.01C-0.1C to 3.8V-4.3V.

[0021] Optionally, the battery cell includes a positive electrode, a negative electrode, a separator and an electrolyte, and the separator is arranged between the positive electrode and the negative electrode.

[0022] Optionally, the positive electrode comprises a positive electrode current collector and a positive electrode material layer stacked on the surface of the positive electrode current collector; the negative electrode comprises a negative electrode current collector and a negative electrode material layer stacked on the surface of the negative electrode current collector;

[0023] The battery core further includes a persulfate layer, and the persulfate layer includes the persulfate;

[0024] The persulfate layer is disposed on a surface of the positive electrode material layer away from the positive electrode current collector; and / or the persulfate layer is disposed on a surface of the negative electrode material layer away from the negative electrode current collector.

[0025] Optionally, the persulfate layer comprises 60 wt.%-100 wt.% of persulfate, 0-20 wt.% of a binder and 0-20 wt.% of a conductive agent.

[0026] Optionally, the positive electrode material layer includes a positive electrode active material; the mass of the persulfate is 0.1%-10% of the mass of the positive electrode active material.

[0027] Optionally, the persulfate includes at least one of sodium persulfate, potassium persulfate, ammonium persulfate, sodium hydrogen persulfate, potassium hydrogen persulfate and ammonium hydrogen persulfate.

[0028] The third aspect of the present application also provides an electrical device, including the lithium-ion battery provided in the first aspect of the present application, or including a battery prepared according to the preparation method provided in the second aspect of the present application. Using the lithium-ion battery provided in the present application to power the device can improve the endurance of the electrical device in a low temperature environment and enhance its market competitiveness. DETAILED DESCRIPTION

[0029] During the formation process of lithium-ion batteries (during the first charge and discharge process), the lithium ions in the system will react with other components in the electrolyte and form a solid electrolyte interface (SEI) film on the surface of the negative electrode and a cathode electrolyte interphase (CEI) film on the surface of the positive electrode. The SEI film generally includes an organic layer and an inorganic layer. The organic layer is mainly composed of organic substances and is located on the surface of the SEI film close to the electrolyte. The inorganic layer mainly includes dense inorganic components and is located on the side of the SEI film close to the negative electrode surface. In lithium-ion batteries, the performance of the SEI film will also play a vital role in the performance of the battery. The ideal SEI film should have a high ionic conductivity. However, in the prior art, the SEI film often increases the lithium ion transfer impedance at the interface and reduces the kinetic performance of the entire battery system. Therefore, improving the structure of the SEI film can also help reduce the battery impedance and improve the low-temperature performance of the battery.

[0030] In the existing lithium-ion battery system, not only the discharge capacity ratio of the phosphate-based positive electrode active material is affected by low temperature, but also other positive electrode active materials, such as ternary positive electrode active materials, will have a corresponding decrease in discharge capacity at low temperature at the same discharge rate. In order to solve the above technical problems, the embodiment of the present application provides a lithium-ion battery, including a negative electrode, the surface of which has a solid electrolyte interface film (SEI);

[0031] Wherein, the solid electrolyte interface film comprises lithium oxide and lithium carbonate;

[0032] The sum of the mass percentages of the lithium oxide and the lithium carbonate in the solid electrolyte interface (SEI) is greater than or equal to 20%.

[0033] In the present application, the above-mentioned lithium carbonate refers specifically to inorganic lithium carbonate (Li 2 CO 3 ).

[0034] In this battery, Li 2 O and Li 2 CO 3 The total proportion of Li in the SEI film is significantly higher than that in the battery SEI film in the prior art. 2 O and Li 2 CO 3 The sum of the mass proportions of Li 2 O and Li 2 CO 3 Has a higher ionic conductivity, so a larger amount of Li 2 O and Li 2 CO 3 Deposition in the SEI film can not only ensure that the inorganic layer in the SEI film is highly dense, but also significantly reduce the impedance of the lithium-ion battery, especially inhibit the impedance growth of the lithium-ion battery when it is cycled in a low-temperature environment, thereby increasing the discharge capacity ratio of the positive electrode active material at low temperatures, improving the low-temperature discharge capability of the lithium-ion battery, and further improving the endurance of the lithium-ion battery at low temperatures, significantly improving the market competitiveness of the lithium-ion battery.

[0035] In addition, reducing the impedance of lithium-ion batteries can also inhibit the polarization effect of lithium-ion batteries.

[0036] In the present application, for example, Li 2 O and Li 2 CO 3The sum of the mass percentages in the SEI film can be 20%, 20.5%, 21.0%, 21.5%, 22.0%, 22.5%, 23.0%, 23.5%, 24.0%, 24.5%, 25.0%, 25.5%, 26.0%, 27.0%, 28.0%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc.

[0037] In the present embodiment, X-ray photoelectron spectroscopy (XPS) can be used to characterize Li 2 O and Li 2 CO 3 The sum of the mass percentages in the SEI film.

[0038] In some embodiments of the present application, Li 2 O and Li 2 CO 3 The sum of the mass percentages of the two in the SEI film is 20%-60%. Controlling the total content of the two within the above range can not only reduce the impedance of the lithium-ion battery and fully inhibit the impedance growth of the lithium-ion battery during the cycle, but also help to ensure that the content of organic matter in the SEI film is more appropriate, thereby benefiting the strength and toughness of the SEI film, and further benefiting the full performance of the battery. For example, Li 2 O and Li 2 CO 3 The sum of the mass percentages in the SEI film can be 20%, 20.5%, 21.0%, 21.5%, 22.0%, 22.5%, 23.0%, 23.5%, 24.0%, 24.5%, 25.0%, 25.5%, 26.0%, 27.0%, 28.0%, 30%, 32.0%, 35.0%, 38.0%, 40.0%, 42.0%, 45.0%, 48.0%, 50%, 52.0%, 55%, 58.0%, and 60%.

[0039] In some embodiments of the present application, Li 2 CO 3 The mass percentage in the SEI membrane is 10%-35%. Lithium carbonate is one of the main inorganic components of the SEI membrane. The ionic conductivity of lithium carbonate is relatively high, so that during the charge and discharge cycle of the battery at room temperature and low temperature, the active lithium ions can be smoothly transferred in the SEI membrane and transferred to the active material in the negative electrode through the SEI membrane, thereby further improving the low-temperature performance of the battery and facilitating the performance of the battery's normal temperature cycle performance. For example, Li 2 CO 3The mass percentage in the SEI film can be 10.0%, 12.0%, 15.0%, 18.0%, 20.0%, 22.0%, 25.0%, 28.0%, 30.0%, 32.0%, 33.0%, 34.0%, etc.

[0040] In some embodiments of the present application, Li 2 The mass percentage of O in the SEI film is 10%-25%. 2 The mass percentage of O in the SEI film can be 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 18.0%, 19.0%, 20.0%, 22.0%, 23.0%, 24.0%, 25.0%, etc. 2 The ionic conductivity of O is relatively low compared to that of Li 2 CO 3 In some specific embodiments, the Li in the SEI film is 2 O and Li 2 CO 3 The mass ratio of Li is in the range of 1:(1-4). In the embodiment of the present application, the ratio of the peak area of ​​the characteristic peak at 526-531 eV of the oxygen fine spectrum in XPS to the total area of ​​the XPS spectrum can be used to characterize Li 2 The mass percentage of O in the SEI film.

[0041] It can be understood that a general lithium-ion battery also includes a positive electrode. In some embodiments of the present application, the surface of the positive electrode has a CEI film, and the CEI film on the surface of the positive electrode includes lithium oxide and lithium carbonate, and Li 2 O and Li 2 CO 3 The sum of the mass percentages of Li in the CEI film is greater than or equal to 20%. When the CEI film also meets the above conditions, it can better cooperate with the SEI film to further reduce the impedance of the lithium-ion battery, thereby further improving the low-temperature performance of the lithium-ion battery, thereby further improving the endurance of the lithium-ion battery at low temperatures. For example, in the CEI film, Li 2 O and Li 2 CO 3 The sum of the mass percentages can be 20.5%, 21.0%, 21.5%, 22.0%, 22.5%, 23.0%, 23.5%, 24.0%, 24.5%, 25.0%, 25.5%, 26.0%, 27.0%, 28.0%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc.

[0042] In some specific embodiments of the present application, Li 2 O and Li 2 CO 3 The total mass percentage of Li in the CEI film is 20%-60%. 2 O and Li 2 CO 3 By controlling the content within the above range, the impedance of the CEI film can be reduced while ensuring good strength and toughness of the CEI film.

[0043] In some embodiments of the present application, Li in the CEI membrane 2 The mass percentage of O is 10%-25%. 2 The mass percentage of O in the CEI film can be 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 18.0%, 19.0%, 20.0%, 22.0%, 23.0%, 24.0%, 25.0%, etc. Similar to the SEI film, this is more conducive to the performance of the battery, which will not be repeated here.

[0044] In some embodiments of the present application, Li in the CEI membrane 2 CO 3 The mass percentage of Li is 10%-35%. 2 CO 3 The mass percentage in the CEI film can be 10.0%, 12.0%, 15.0%, 18.0%, 20.0%, 22.0%, 25.0%, 28.0%, 30.0%, 32.0%, 33.0%, 34.0%, etc. Similar to the SEI film, this is more conducive to the performance of the battery, which will not be repeated here.

[0045] In some embodiments of the present application, the positive electrode includes a positive electrode current collector and a positive electrode material layer stacked on the surface of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes at least one of a phosphate-based positive electrode active material and a transition metal oxide positive electrode active material. Among them, the phosphate-based positive electrode active material includes but is not limited to one or more of materials such as doped or undoped lithium iron phosphate and lithium iron manganese phosphate, and the transition metal oxide positive electrode active material includes but is not limited to one or more of materials such as doped or undoped ternary materials and lithium-rich layered oxides.

[0046] The present application provides a method for preparing a lithium ion battery. The method for preparing a lithium ion battery includes:

[0047] Providing a battery cell; and, persulfate is added to the battery cell;

[0048] The battery cell is subjected to chemical formation to obtain a lithium-ion battery.

[0049] As a strong oxidant, persulfate decomposes to produce oxygen, ozone and other substances during the formation process of the battery cell. The above substances diffuse into the battery cell and react with other substances in the system (for example, electrolytes, etc.) to form oxygen free radicals. The oxygen free radicals further react with lithium ions in the system (for example, lithium ions in the electrolyte, lithium ions released by the positive electrode active material, etc.), oxidizing the lithium ions to Li 2 O, and generate a certain amount of Li 2 CO 3 , the generated Li 2 O and Li 2 CO 3 Further deposited in the SEI film; it can be understood that the above oxidation reaction is a competitive reaction, Li 2 O and Li 2 CO 3 The production of will reduce the proportion of other substances (for example, reducing the production of substances such as alkyl lithium), thereby improving the structure of the SEI film, thereby improving the battery's endurance at low temperatures, and significantly improving the battery's market competitiveness.

[0050] In some embodiments of the present application, in the SEI film of the prepared lithium-ion battery, the sum of the mass percentages of lithium oxide and lithium carbonate is greater than or equal to 20%.

[0051] It can be understood that the battery cell may include a positive electrode, a negative electrode, a separator and an electrolyte, and the separator is arranged between the positive electrode and the negative electrode; or, the battery cell may include a positive electrode, a negative electrode and a solid electrolyte, and the solid electrolyte is arranged between the positive electrode and the negative electrode; or, the battery cell may include a positive electrode, a negative electrode, a solid electrolyte and an electrolyte, and the solid electrolyte is arranged between the positive electrode and the negative electrode; or, the battery cell may include a positive electrode, a negative electrode and a gel electrolyte, and the gel electrolyte is arranged between the positive electrode and the negative electrode. Persulfate is added to the battery cell, and the persulfate can be added to any of the above components in the battery cell. For example, when the battery cell includes a positive electrode, a negative electrode, a separator and an electrolyte, persulfate can be added to at least one of the positive electrode, the negative electrode, the separator and the electrolyte; when the battery cell includes a positive electrode, a negative electrode and a solid electrolyte, persulfate can be added to at least one of the positive electrode, the negative electrode and the solid electrolyte; when the battery cell includes a positive electrode, a negative electrode, a solid electrolyte and an electrolyte, persulfate can be added to at least one of the positive electrode, the negative electrode, the solid electrolyte and the electrolyte; when the battery cell includes a positive electrode, a negative electrode and a gel electrolyte, persulfate can be added to at least one of the positive electrode, the negative electrode and the gel electrolyte.

[0052] The main difference between the "battery cell" in this application and the "lithium-ion battery" is that the battery cell has not been formed.

[0053] In some embodiments of the present application, the lithium ion battery prepared by the preparation method provided in the embodiments of the present application is the aforementioned lithium ion battery provided in the embodiments of the present application.

[0054] In some embodiments of the present application, during the formation process of the battery cell, a Li 2 O and Li 2 CO 3 The CEI film. The formation principle is similar to that of the SEI film, which will not be described here. In this way, it is more conducive to reducing the impedance of the final lithium-ion battery, thereby further improving the low-temperature performance of the lithium-ion battery.

[0055] In some embodiments of the present application, the battery cell includes a positive electrode, a negative electrode, a separator and an electrolyte, and the separator is arranged between the positive electrode and the negative electrode of the battery cell. At this time, the persulfate may be present in at least one of the above-mentioned positive electrode, the above-mentioned negative electrode, the above-mentioned separator and the above-mentioned electrolyte. In some specific embodiments, in the battery cell, the persulfate is loaded in the positive electrode and / or the negative electrode. Specifically, in the battery cell, the positive electrode includes a positive electrode collector and a positive electrode material layer arranged on the surface of the positive electrode collector; the negative electrode includes a negative electrode collector and a negative electrode material layer arranged on the surface of the negative electrode collector. The persulfate can be dispersed in the positive electrode material layer and / or the negative electrode material layer, or it can be prepared separately as a persulfate layer. Among them, in the battery cell, the persulfate layer can be arranged between the positive electrode collector and the positive electrode material layer, or it can be arranged on the surface of the positive electrode material layer away from the positive electrode collector; the persulfate layer can be arranged between the negative electrode collector and the negative electrode material layer, or it can be arranged on the surface of the negative electrode material layer away from the negative electrode collector. Correspondingly, the lithium-ion battery obtained by the above-mentioned battery cell formation is a liquid lithium-ion battery using an electrolyte, and a separator is also provided between the positive electrode and the negative electrode in the lithium-ion battery.

[0056] In some specific embodiments of the present application, in the battery cell, the persulfate layer is disposed on the surface of the positive electrode material layer away from the positive electrode current collector, and / or the persulfate layer is disposed on the surface of the negative electrode material layer away from the negative electrode current collector. In this way, the gas generated after the decomposition of the persulfate can be fully avoided to affect the structure of the positive electrode material layer and / or the negative electrode material layer, thereby being more conducive to the performance of the battery.

[0057] In some embodiments of the present application, the persulfate includes but is not limited to at least one of sodium persulfate, potassium persulfate, ammonium persulfate, sodium hydrogen persulfate, potassium hydrogen persulfate and ammonium hydrogen persulfate. The above substances can not only be fully decomposed to generate O during the formation process of the battery 2 and / or 3, and the generation of other products will not affect the performance of the battery, thus facilitating the normal performance of the battery. In addition, the decomposition potential of the persulfate matches the potential of the battery formation, and can be stably present during the preparation process of the battery cell (including the drying and baking that may be involved in the preparation process of the positive and negative electrodes).

[0058] In the embodiment of the present application, the positive electrode current collector may be any positive electrode current collector known in the art, including but not limited to aluminum foil. In the embodiment of the present application, the negative electrode current collector includes but is not limited to a negative electrode current collector, including but not limited to copper foil.

[0059] In the embodiment of the present application, the positive electrode active material in the positive electrode material layer can be any positive electrode active material for lithium-ion batteries known in the art. Exemplarily, in some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode material layer stacked on the surface of the positive electrode current collector, and the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes at least one of a phosphate-based positive electrode active material and a transition metal oxide positive electrode active material. Among them, the phosphate-based positive electrode active material includes but is not limited to one or more of doped or undoped lithium iron phosphate, lithium manganese iron phosphate and other materials, and the transition metal oxide positive electrode active material includes but is not limited to one or more of doped or undoped ternary materials, lithium-rich layered oxides and other materials.

[0060] In the embodiment of the present application, the negative electrode active material in the negative electrode material layer can be any negative electrode active material for lithium-ion batteries known in the art. Exemplarily, the negative electrode active material can be selected from one or more of carbon-based negative electrode active materials, silicon-based negative electrode active materials, tin-based negative electrode active materials, and lithium metal negative electrode active materials. Among them, the carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, etc.; the silicon-based negative electrode may include silicon, silicon carbon, silicon oxygen, silicon metal compounds, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds, but is not limited thereto.

[0061] In the embodiment of the present application, the conductive agent can be any conductive agent known in the art. For example, the conductive agent includes but is not limited to at least one of super P, acetylene black, graphene, and carbon nanotubes, but is not limited thereto.

[0062] In the embodiment of the present application, the above-mentioned binder can be any binder known in the art. For example, the binder includes but is not limited to at least one of sodium hydroxycellulose (CMC), polyvinylidene fluoride (PVDF), and styrene-butadiene rubber (SBR), but is not limited thereto.

[0063] In some embodiments of the present application, the persulfate layer includes 60wt.%-100wt.% of persulfate, 0-20wt.% of a binder and 0-20wt.% of a conductive agent. In some specific embodiments, the persulfate layer includes persulfate, a binder and a conductive agent. At this time, the persulfate layer includes 60wt.%-100wt.% of persulfate, 1wt.%-20wt.% of a binder and 1wt.%-20wt.% of a conductive agent. It can be understood that the formation process of the battery is generally pressurized. In this way, after the persulfate is decomposed, under the pressure applied to the battery cell during the formation process, the conductive agent and the binder will also adhere to the positive electrode active material layer and participate in the formation of the positive electrode conductive network, thereby facilitating the performance of the battery. Exemplarily, the mass percentage of persulfate in the persulfate layer may be 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 98%, 100%, etc. Exemplarily, the mass percentage of binder in the persulfate layer may be 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc. Exemplarily, the mass percentage of conductive agent in the persulfate layer may be 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc.

[0064] In some other embodiments of the present application, the persulfate layer is composed only of persulfate. It is understandable that the formation process of the battery is generally subjected to a pressurization process. In this way, during the formation process of the battery, the persulfate layer is completely decomposed, and under the action of pressure, the negative electrode, the separator and the positive electrode can be laminated, thereby ensuring the structural stability of the final lithium-ion battery.

[0065] In the embodiment of the present application, the conductive agent can be any conductive agent known in the art. For example, the conductive agent includes but is not limited to at least one of super P, acetylene black, graphene, and carbon nanotubes, but is not limited thereto.

[0066] In the embodiment of the present application, the above-mentioned binder can be any binder known in the art. For example, the binder includes but is not limited to at least one of sodium hydroxycellulose (CMC), polyvinylidene fluoride (PVDF), and styrene-butadiene rubber (SBR), but is not limited thereto.

[0067] In the embodiment of the present application, in the battery cell, the positive electrode material layer, the negative electrode material layer and the optional persulfate layer may further include a dispersant. The dispersant may also be any dispersant known in the art, including but not limited to polyvinyl pyrrolidone (PVP).

[0068] In the embodiment of the present application, in the battery cell, the positive electrode may contain persulfate, the negative electrode may contain persulfate, or both the positive electrode and the negative electrode may contain persulfate. The distribution position of the persulfate does not affect the generation of lithium carbonate and lithium oxide and their deposition in the SEI film. Taking the persulfate loaded in the positive electrode as an example, during the battery cell formation process, the decomposition products of the persulfate in the positive electrode react with the lithium ions in the system to generate Li 2 O and Li 2 CO 3 It can be smoothly deposited into the SEI film, and further, it can be smoothly deposited into the CEI film.

[0069] In some embodiments of the present application, the mass of the persulfate in the battery cell accounts for 0.1%-10% of the mass of the positive electrode active material in the battery cell. In this way, the SEI film in the lithium-ion battery after formation can have sufficient lithium oxide and lithium carbonate, and it is also beneficial to reduce the risk of large-scale decomposition and gas production of persulfate affecting the structural stability of the positive and negative electrodes. In addition, controlling the mass proportion of persulfate within the above range and squeezing out the share of the positive electrode active material is beneficial to the energy density of the battery and will not affect the construction of the conductive network of the positive electrode before / after formation, thereby ensuring good cycle performance of the battery. Further, in some specific embodiments, the mass of the persulfate in the battery cell accounts for 0.2%-2% of the mass of the positive electrode active material in the battery cell. In this way, while reducing the impedance of the lithium-ion battery and improving its low-temperature performance, the energy density and cycle performance of the lithium-ion battery are taken into account. Exemplarily, the mass of persulfate in the battery cell can account for 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, etc., of the mass of the positive electrode active material in the battery cell.

[0070] Alternatively, the amount of persulfate added to the battery cell can also be measured according to the total content of the negative electrode active material in the battery cell. In some embodiments of the present application, the mass of the persulfate in the battery cell accounts for 0.1%-10% of the mass of the negative electrode active material in the battery cell. Further, in some specific embodiments, the mass of the persulfate in the battery cell accounts for 0.2%-2% of the mass of the negative electrode active material in the battery cell. Exemplarily, the mass of persulfate in the battery cell can account for 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, etc., of the mass of the negative electrode active material in the battery cell.

[0071] Alternatively, in a liquid battery using an electrolyte, the amount of persulfate added to the battery cell can also be measured based on the electrolyte. In some embodiments of the present application, the mass concentration of persulfate in the electrolyte is 0.1%-10% based on the total mass of the electrolyte in the battery cell. Exemplarily, the mass of persulfate in the battery cell can account for 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, etc. of the mass of the electrolyte in the battery cell.

[0072] In some embodiments of the present application, the preparation method of the positive electrode loaded with persulfate in the battery cell includes but is not limited to at least one of (a) and (b):

[0073] (a) dispersing a positive electrode active material, a binder and a conductive agent in a solvent and mixing them to obtain a positive electrode slurry;

[0074] Dispersing persulfate, a binder and a conductive agent in a solvent and mixing them to obtain a persulfate slurry;

[0075] The positive electrode slurry is coated on the positive electrode collector and dried to obtain a positive electrode material layer; the persulfate slurry is then coated on the surface of the positive electrode material layer, dried, rolled, and cut to obtain a positive electrode; or the persulfate slurry is coated on the positive electrode collector and dried to obtain a persulfate layer; the positive electrode slurry is then coated on the surface of the persulfate layer, dried, rolled, and cut to obtain a positive electrode of the battery cell.

[0076] (b) dispersing the positive electrode active material, the binder, the conductive agent and the persulfate in a solvent, and mixing them to obtain a positive electrode slurry containing persulfate; coating the slurry on the surface of the positive electrode current collector, and obtaining the positive electrode of the battery cell through drying, rolling and cutting.

[0077] In some embodiments of the present application, the solvent used in the above step (a) and step (b) includes but is not limited to at least one of N-methylpyrrolidone (NMP).

[0078] Similarly, in some other embodiments of the present application, the preparation method of the negative electrode loaded with persulfate in the battery cell includes but is not limited to (1) and (2):

[0079] (1) A negative electrode material layer and a persulfate layer are sequentially formed on the surface of the negative electrode current collector; or, a persulfate layer and a negative electrode material layer are sequentially formed on the surface of the negative electrode current collector. The specific preparation process can be adapted according to the above-mentioned positive electrode preparation step (a), which will not be repeated here.

[0080] (2) First prepare the negative electrode slurry containing persulfate, and then coat the negative electrode slurry containing persulfate on the surface of the negative electrode current collector. The specific preparation process can be adapted according to the above-mentioned positive electrode preparation step (b), which will not be repeated here.

[0081] In some embodiments of the present application, the solvent used in the above steps (1) and (2) includes but is not limited to water and / or NMP. At this time, the above-mentioned electrolyte can be any electrolyte known in the art. In some embodiments, the electrolyte includes a solvent, an electrolyte salt and optional additives. In other embodiments, the electrolyte includes a solvent, an electrolyte salt, a persulfate and optional additives. Exemplarily, the above-mentioned solvent includes but is not limited to carbonate solvents, and carbonate solvents include but are not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), etc. Exemplarily, the electrolyte salt includes but is not limited to lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium sulfate (Li 2 SO 4 ), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluoroarsenate (LiAsF 6 ), lithium trifluoromethanesulfonate (LiTFA or LiOTF), and lithium perchlorate (LiClO 4). For example, the additive can be selected from negative electrode film-forming additives familiar to those skilled in the art. The additive can be selected according to actual application needs.

[0082] In some embodiments of the present application, the positive electrode, the negative electrode and the separator are stacked so that the separator is placed between the positive electrode and the negative electrode to assemble a dry battery cell; an electrolyte is injected into the dry battery cell, and the electrolyte is allowed to fully infiltrate the positive and negative electrodes to obtain a battery cell, which is then chemically formed.

[0083] In some embodiments of the present application, the battery cell is placed at a temperature of 20°C-70°C for formation. Further, in some specific embodiments, the battery cell is placed at a temperature of 45°C-60°C for formation. In this way, the rate of decomposition of persulfate is faster, which can reduce the polarization of the battery during the decomposition of persulfate; at the same time, the formation at the above temperature is also conducive to the formation of organic matter in the SEI film and the CEI film, and makes the SEI film and the CEI film have a suitable thickness, thereby facilitating the improvement of the overall performance of the final battery. Exemplarily, the formation temperature of the battery cell can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 48°C, 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, 70°C, etc.

[0084] In some embodiments of the present application, during the formation process, the charging method used includes:

[0085] S01. The battery cell is charged at a constant current of 0.03C-0.1C to 10% SOC-20% SOC; wherein, the battery cell can be charged at a current density of but not limited to 0.03C, 0.05C, 0.06C, 0.07C, 0.08C, 0.09C, 0.10C, etc., to a charge state of 10% SOC, 12% SOC, 15% SOC, 18% SOC, 20% SOC, etc.; in this way, a SEI film with a higher degree of density is formed on the surface of the negative electrode, and the density of the CEI film is also improved, thereby improving the performance of the battery.

[0086] S02, 0.2C-0.5C constant current charging to 3.5V-3.8V; illustratively, the battery cell can be charged with a current density of, but not limited to, 0.20C, 0.25C, 0.30C, 0.35C, 0.40C, 0.45C, 0.50C to a voltage of 3.50V, 3.55V, 3.60V, 3.65V, 3.70V, 3.75V, 3.80V. In this way, it is beneficial to save the time of the formation process and improve production efficiency.

[0087] S03, charging at a constant current of 0.01C-0.1C to 3.8V-4.3V; illustratively, the battery cell may be charged at a current density of, but not limited to, 0.01C, 0.02C, 0.03C, 0.05C, 0.06C, 0.07C, 0.08C, 0.09C, 0.10C to a voltage of 3.8V, 3.9V, 4.0V, 4.1V, 4.2V, 4.3V, etc. In this way, it is beneficial to promote the decomposition of excess additives in the battery cell (for example, film-forming additives that do not participate in the reaction, excess persulfate, etc.), and avoid excess electrochemically inactive additives from affecting the performance of the battery.

[0088] In some embodiments of the present application, the formed battery cells are subjected to the steps of exhausting, replenishing, charging, aging, and capacity separation in sequence to obtain a lithium-ion battery.

[0089] The method for preparing a lithium-ion battery provided in the embodiment of the present application can prepare the aforementioned lithium-ion battery provided in the embodiment of the present application.

[0090] In the embodiment of the present application, the lithium-ion battery may be a wound battery or a laminated battery.

[0091] The present application also provides an electric device, including the lithium-ion battery provided in the present application. Since the lithium-ion battery provided in the present application is used to power the device, the electric device has good endurance in a low temperature environment and strong market competitiveness.

[0092] In some embodiments of the present application, the above-mentioned electrical equipment includes but is not limited to 3C electronic consumer products such as vehicles, mobile phones, laptops, tablets, smart watches, etc.

[0093] The technical solution of the present application is described in detail below with multiple embodiments.

[0094] Example 1

[0095] (1) Preparing a positive electrode: mixing a positive electrode active material (specifically lithium iron phosphate), a conductive agent (specifically carbon nanotubes), a binder (specifically PVDF), a persulfate (specifically sodium persulfate) and a solvent (specifically NMP) in a mass ratio of 100:1:2.5:0.2:50 to obtain a positive electrode slurry containing persulfate; coating the slurry on the surface of a positive electrode current collector (specifically aluminum foil), and obtaining a positive electrode after drying, rolling and slitting.

[0096] (2) Preparing a negative electrode: mixing a negative electrode active material (specifically graphite), a conductive agent (specifically carbon black), a first binder (specifically CMC), a second binder (specifically SBR) and a solvent (specifically water) in a mass ratio of 100:1:1.6:1.2:110 to obtain a negative electrode slurry; coating the negative electrode slurry on the surface of a negative electrode current collector (specifically copper foil), and obtaining a negative electrode after drying, rolling and slitting.

[0097] (3) The positive electrode, separator (specifically, a PP separator with a thickness of 14 μm) and negative electrode are stacked in sequence to form a dry cell; the electrolyte is injected into the dry cell and placed at 25°C for formation, and then the dry cell is sealed after exhaust, liquid replenishment, charging, aging, capacity division, and self-discharge testing to obtain the lithium-ion battery of Example 1. The electrolyte is 1 mol LiPF 6 Dissolved in EC:DMC:DEC:EMC:VC with a mass ratio of 30:30:10:10:3. The charging method used in the battery cell formation process is: charging the battery cell with a constant current of 0.1C to 10% SOC, then charging the battery cell with a constant current of 0.4C to 3.8V, and then charging the battery cell with a constant current of 0.1C to 4.3V.

[0098] In lithium-ion batteries, the mass percentage of lithium oxide in the SEI film is 15.2%, and the mass percentage of lithium carbonate is 20.4%.

[0099] Example 2

[0100] The difference from Example 1 is that step (1) is: mixing a positive electrode active material (specifically lithium iron phosphate), a conductive agent (specifically carbon nanotubes), a binder (specifically PVDF) and a solvent (specifically NMP) in a mass ratio of 100:1:2.5:50 to obtain a positive electrode slurry; coating the positive electrode slurry on the surface of the positive electrode current collector (specifically aluminum foil), and controlling the surface density of the positive electrode active material to 200 g / m 2 , drying to form a positive electrode material layer;

[0101] Persulfate (specifically sodium persulfate), super-P, PVDF and NMP were mixed in a mass ratio of 10:1:1 to prepare a persulfate slurry with a solid content of 10%, which was sprayed on the surface of the positive electrode material layer, and the surface density of sodium persulfate was controlled to be 0.4 g / m 2 The positive electrode is obtained after baking, drying, rolling and cutting. The mass of sodium persulfate is 0.2% of the mass of the positive electrode active material.

[0102] In lithium-ion batteries, the mass percentage of lithium oxide in the SEI film is 17.6%, and the mass percentage of lithium carbonate is 23.4%.

[0103] Example 3

[0104] The difference from Example 2 is that the battery cell is formed at 50°C.

[0105] In lithium-ion batteries, the mass percentage of lithium oxide in the SEI film is 19.4%, and the mass percentage of lithium carbonate is 24.6%.

[0106] Example 4

[0107] The only difference from Example 3 is that the order of step (1) in Example 2 is slightly adjusted, and the persulfate layer is located between the positive electrode current collector and the positive electrode material layer.

[0108] In lithium-ion batteries, the mass percentage of lithium oxide in the SEI film is 12.7%, and the mass percentage of lithium carbonate is 20.7%.

[0109] Example 5

[0110] The only difference from Example 3 is that the mass of the persulfate in the battery core is 2.0% of the mass of the positive electrode active material.

[0111] In lithium-ion batteries, the mass percentage of lithium oxide in the SEI film is 24.4%, and the mass percentage of lithium carbonate is 26.5%.

[0112] Example 6

[0113] The only difference from Example 3 is that the mass of the persulfate in the battery core is 10.0% of the mass of the positive electrode active material.

[0114] In lithium-ion batteries, the mass percentage of lithium oxide in the SEI film is 28.7%, and the mass percentage of lithium carbonate is 26.8%.

[0115] Example 7

[0116] The difference from Example 3 is that the mass of the persulfate in the battery core is 0.1% of the mass of the positive electrode active material.

[0117] In lithium-ion batteries, the mass percentage of lithium oxide in the SEI film is 10.2%, and the mass percentage of lithium carbonate is 11.4%.

[0118] Example 8

[0119] The difference from Example 3 is that the mass of the persulfate in the battery core is 12.0% of the mass of the positive electrode active material.

[0120] In lithium-ion batteries, the mass percentage of lithium oxide in the SEI film is 25.4%, and the mass percentage of lithium carbonate is 40.5%.

[0121] Example 9

[0122] The difference from Example 3 is that the battery cell is formed at 65°C.

[0123] In lithium-ion batteries, the mass percentage of lithium oxide in the SEI film is 20.4%, and the mass percentage of lithium carbonate is 44.6%.

[0124] Example 10

[0125] The difference from Example 3 is that the battery cell is formed at 75°C.

[0126] In lithium-ion batteries, the mass percentage of lithium oxide in the SEI film is 24.1%, and the mass percentage of lithium carbonate is 57.6%.

[0127] Embodiment 11

[0128] The difference from Example 3 is that the charging method used in the battery cell formation process is different: the battery cell is charged to 20% SOC at a current density of 0.2C, then charged to 3.65V at a constant current of 0.6C, and then charged to 4.2V at a constant current of 0.2C.

[0129] Example 12

[0130] (1) Preparation of positive electrode: A positive electrode active material (specifically lithium iron phosphate), a conductive agent (specifically carbon nanotubes), a binder (specifically PVDF) and a solvent (specifically NMP) are mixed in a mass ratio of 100:1:2.5:50 to obtain a positive electrode slurry; the positive electrode slurry is coated on the surface of a positive electrode current collector (specifically aluminum foil), and after drying, rolling and slitting, a positive electrode is obtained.

[0131] (2) Preparation of negative electrode: A negative electrode active material (specifically graphite), a conductive agent (specifically carbon black), a first binder (specifically CMC), a second binder (specifically SBR), a persulfate (specifically sodium persulfate) and a solvent (specifically water) are mixed in a mass ratio of 100:1:1.6:1.2:0.3:110 to obtain a negative electrode slurry containing persulfate; the slurry is coated on the surface of a negative electrode current collector (specifically copper foil), and after drying, rolling and slitting, a negative electrode is obtained.

[0132] (3) The positive electrode, separator (specifically, a PP separator with a thickness of 14 μm) and negative electrode are stacked in sequence to form a dry cell; the electrolyte is injected into the dry cell and placed at 25°C for formation, and then sealed after exhaust, liquid replenishment, charging, aging, capacity division, and self-discharge testing to obtain the lithium-ion battery of Example 1. The electrolyte is 1 mol LiPF 6Dissolved in EC:DMC:DEC:EMC:VC with a mass ratio of 30:30:10:10:3. The charging method used in the battery cell formation process is: charging the battery cell with a constant current of 0.1C to 10% SOC, then charging the battery cell with a constant current of 0.4C to 3.8V, and then charging the battery cell with a constant current of 0.1C to 4.3V.

[0133] In lithium-ion batteries, the mass percentage of lithium oxide in the SEI film is 14.7%, and the mass percentage of lithium carbonate is 19.5%.

[0134] Embodiment 13

[0135] The difference from Example 12 is that the battery cell is formed at 50°C.

[0136] In lithium-ion batteries, the mass percentage of lithium oxide in the SEI film is 16.8%, and the mass percentage of lithium carbonate is 24.6%.

[0137] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.

[0138] Comparative Example 1

[0139] (1) Preparation of positive electrode: A positive electrode active material (specifically lithium iron phosphate), a conductive agent (specifically carbon nanotubes), a binder (specifically PVDF) and a solvent (specifically NMP) are mixed in a mass ratio of 100:1:2.5:50 to obtain a positive electrode slurry; the positive electrode slurry is coated on the surface of a positive electrode current collector (specifically aluminum foil), and after drying, rolling and slitting, a positive electrode is obtained.

[0140] (2) Preparing a negative electrode: mixing a negative electrode active material (specifically graphite), a conductive agent (specifically carbon black), a first binder (specifically CMC), a second binder (specifically SBR) and a solvent (specifically water) in a mass ratio of 100:1:1.6:1.2:110 to obtain a negative electrode slurry; coating the negative electrode slurry on the surface of a negative electrode current collector (specifically copper foil), and obtaining a negative electrode after drying, rolling and slitting.

[0141] (3) The positive electrode, separator (specifically, a PP separator with a thickness of 14 μm) and negative electrode are stacked in sequence to form a dry cell; the electrolyte is injected into the dry cell and placed at 25°C for formation, and then sealed after exhaust, liquid replenishment, charging, aging, capacity division, and self-discharge testing to obtain the lithium-ion battery of Example 1. The electrolyte is 1 mol LiPF 6Dissolved in EC:DMC:DEC:EMC:VC with a mass ratio of 30:30:10:10:3. The charging method used in the battery cell formation process is: charging the battery cell with a constant current of 0.1C to 10% SOC, then charging the battery cell with a constant current of 0.4C to 3.8V, and then charging the battery cell with a constant current of 0.1C to 4.3V.

[0142] In lithium-ion batteries, the sum of the mass percentages of lithium oxide and lithium carbonate in the SEI film is 18.6%.

[0143] Performance Testing

[0144] (1) Capacity retention rate test of each embodiment and comparative example battery at different temperatures:

[0145] The batteries of each embodiment and comparative example were subjected to charge and discharge cycle tests at 25°C, 10°C, 0°C, -10°C, and -20°C, respectively. Specifically, the charge and discharge cycle test conditions under each condition were: charging to 3.8V at 0.33C constant current, charging to 0.05C cut-off at constant voltage; standing for 10 minutes; discharging to 2.0V at 0.33C constant current, i.e., one cycle. Repeat this step to test the capacity retention rate of the battery after 500 cycles.

[0146] Taking the cycle retention rate at 25°C as a benchmark, the cycle retention rates at other temperatures were calculated as percentages relative to the cycle retention rate at 25°C. The calculation results are summarized in Table 1.

[0147] Table 1

[0148]

[0149] From the data in Table 1, it can be found that the low-temperature performance of the battery provided in the embodiment of the present application, especially the percentage of the cycle retention rate below 0°C relative to room temperature, is significantly higher than that of the battery in Comparative Example 1. In addition, it can be seen from the data between the examples that when the total content of lithium carbonate and lithium oxide in the SEI film is within the range more recommended in this application (Examples 1-3, 5-7), not only the cycle performance of each battery below 25°C is better, but also the cycle capacity retention rate of the battery at 25°C can be improved. Further, by comparing the results of Examples 5 and 6, it can be found that when the total content of lithium carbonate and lithium oxide in the SEI film is similar, when the respective contents of lithium carbonate and lithium oxide are within the range further recommended in this application (Example 5), the battery has better cycle performance below 25°C.

[0150] By comparing the data of Example 3 and Example 4, it can be found that in the preparation process of the battery, when the persulfate layer is arranged on the surface of the positive electrode away from the current collector, it is more conducive to reducing the battery impedance and improving the battery's cycle performance at various temperatures. By comparing the data of Examples 3, 10 and 11, it is not difficult to see that in the preparation process of the lithium-ion battery, the formation temperature further recommended in this application is more conducive to the performance of the battery. And adopting the charging strategy recommended in this application during the formation process is also more conducive to the performance of the SEI film and to improving the battery's cycle performance at room temperature and low temperature.

[0151] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A lithium ion battery, characterized in that: The invention comprises a negative electrode, wherein the surface of the negative electrode has a solid electrolyte interface film; Wherein, the solid electrolyte interface film comprises lithium oxide and lithium carbonate; The sum of the mass percentages of the lithium oxide and the lithium carbonate in the solid electrolyte interface film is greater than or equal to 20%.

2. The lithium-ion battery according to claim 1, characterized in that The sum of the mass percentages of the lithium oxide and the lithium carbonate in the solid electrolyte interface film is 20%-60%.

3. The lithium ion battery according to claim 1 or 2, characterized in that: The mass percentage of the lithium oxide in the solid electrolyte interface film is 10%-25%.

4. The lithium ion battery according to claim 1 or 2, characterized in that: The mass percentage of the lithium carbonate in the solid electrolyte interface film is 10%-35%.

5. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The lithium-ion battery also includes a positive electrode, the surface of which has a positive electrode electrolyte interface film; wherein the positive electrode electrolyte interface film includes lithium oxide and lithium carbonate; the sum of the mass percentages of lithium oxide and lithium carbonate in the positive electrode electrolyte interface film is greater than or equal to 20%.

6. The lithium ion battery according to any one of claims 1 to 5, characterized in that: The lithium-ion battery also includes a positive electrode, which includes a positive electrode collector and a positive electrode material layer stacked on the surface of the positive electrode collector. The positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes at least one of a phosphate-based positive electrode active material and a transition metal oxide positive electrode active material.

7. A method for preparing a lithium ion battery, characterized in that: include: Provide battery cells; Furthermore, persulfate is added to the battery cell; The battery core is chemically formed to obtain the lithium-ion battery.

8. The method for preparing a lithium ion battery according to claim 7, characterized in that: The formation temperature is in the range of 20°C-70°C.

9. The method for preparing a lithium ion battery according to claim 7, characterized in that: The charging method adopted in the formation includes: The battery cell is charged at a constant current of 0.03C-0.1C to 10% SOC-20% SOC, then charged at a constant current of 0.2C-0.5C to 3.5V-3.8V, and then charged at a constant current of 0.01C-0.1C to 3.8V-4.3V.

10. The method for preparing a lithium ion battery according to claim 7, characterized in that: The battery cell comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the separator is arranged between the positive electrode and the negative electrode.

11. The method for preparing a lithium ion battery according to claim 10, characterized in that: The positive electrode comprises a positive electrode current collector and a positive electrode material layer stacked on the surface of the positive electrode current collector; the negative electrode comprises a negative electrode current collector and a negative electrode material layer stacked on the surface of the negative electrode current collector; The battery core further includes a persulfate layer, and the persulfate layer includes the persulfate; The persulfate layer is disposed on the surface of the positive electrode material layer away from the positive electrode current collector; And / or, the persulfate layer is disposed on a surface of the negative electrode material layer away from the negative electrode current collector.

12. The method for preparing a lithium ion battery according to claim 11, characterized in that: The persulfate layer includes 60wt.%-100wt.% of persulfate, 0-20wt.% of a binder and 0-20wt.% of a conductive agent.

13. The method for preparing a lithium ion battery according to claim 11 or 12, characterized in that: The positive electrode material layer includes a positive electrode active material; the mass of the persulfate is 0.1%-10% of the mass of the positive electrode active material.

14. The method for preparing a lithium ion battery according to any one of claims 7 to 13, characterized in that: The persulfate includes at least one of sodium persulfate, potassium persulfate, ammonium persulfate, sodium hydrogen persulfate, potassium hydrogen persulfate and ammonium hydrogen persulfate.

15. The method for preparing a lithium ion battery according to any one of claims 7 to 14, characterized in that: The lithium ion battery is a lithium ion battery as claimed in any one of claims 1 to 6.

16. An electrical equipment, characterized in that: The electrical equipment comprises a lithium-ion battery as described in any one of claims 1 to 6, or comprises a lithium-ion battery prepared by the preparation method as described in any one of claims 7 to 15.